2003
DOI: 10.1016/s0891-5849(03)00468-4
|View full text |Cite
|
Sign up to set email alerts
|

Two subpopulations of mitochondria in the aging rat heart display heterogenous levels of oxidative stress

Abstract: Cardiac mitochondria are composed of two distinct subpopulations: one beneath the sarcolemma (subsarcolemmal mitochondria: SSM), and another along the myofilaments (interfibrillary mitochondria: IFM). Previous studies suggest a preferential loss of IFM function with age; however, the age-related changes in oxidative stress in these mitochondrial subpopulations have not been examined. To this end, the changes in mitochondrial antioxidant capacity, oxidant output, and oxidative damage to Complex IV in IFM and SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
78
3
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 47 publications
16
78
3
1
Order By: Relevance
“…Data from our laboratory indicate that H 2 O 2 production by SSM, but not IFM, increases with age (87). These results are in contrast with previous findings by Suh et al (175) who reported an age-dependent increase in oxidant production by IFM but not SSM isolated from rat hearts. This seemingly opposite evidence could stem from methodological differences between the two studies with regard to the assessment of mitochondrial oxidant production: rate of oxidation of 2'7'-dihydrodichlorofluorescein that detects a variety of intramitochondrial oxidants [including H 2 O 2 and nitric oxide (NO · )] (175) as opposed to the quantification of H 2 O 2 released from intact mitochondria (87).…”
Section: Mechanisms Of Mitochondrial Dysfunction and Altered Mitochoncontrasting
confidence: 95%
See 1 more Smart Citation
“…Data from our laboratory indicate that H 2 O 2 production by SSM, but not IFM, increases with age (87). These results are in contrast with previous findings by Suh et al (175) who reported an age-dependent increase in oxidant production by IFM but not SSM isolated from rat hearts. This seemingly opposite evidence could stem from methodological differences between the two studies with regard to the assessment of mitochondrial oxidant production: rate of oxidation of 2'7'-dihydrodichlorofluorescein that detects a variety of intramitochondrial oxidants [including H 2 O 2 and nitric oxide (NO · )] (175) as opposed to the quantification of H 2 O 2 released from intact mitochondria (87).…”
Section: Mechanisms Of Mitochondrial Dysfunction and Altered Mitochoncontrasting
confidence: 95%
“…It is noteworthy that in IFM from the same animals, Judge et al (87) also observed increased activities of several antioxidant enzymes (SOD, GPX, and catalase), reduced glutathione concentrations, and elevated levels of oxidative damage. These findings may suggest that oxidant production within the matrix of old IFM is greater than in younger counterparts, which is in agreement with the results by Suh et al (175).…”
Section: Mechanisms Of Mitochondrial Dysfunction and Altered Mitochonsupporting
confidence: 93%
“…Moreover, differences in the activities of OxPhos complexes in the literature could result from the use of different subpopulations of mitochondria in different studies (Fannin et al, 1999;Palmer et al, 1977). It has been previously demonstrated that interfibrillar mitochondria exhibit a selective decline in Complex III and IV activity which is not observed in the subsarcolemmal population of mitochondria (Fannin et al, 1999;Lesnefsky and Hoppel, 2006;Suh et al, 2003). In our study, mitochondria were not separated and a mixed population was used, therefore any selective decrease in the activity of ETC complexes in one subpopulation could have been masked.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are two distinct mitochondrial subpopulations in the cardiac myocytes, SSM and IMF, similar to that found in skeletal muscle. The two populations of mitochondria response differently to physiological stimuli including obesity, diabetes, aging, fasting, apoptosis, and ischemia-reperfusion injury (Lesnefsky et al, 2001;Suh et al, 2003;Ritov et al, 2005;Mollica et al, 2006). John M. Hollander's research group investigated thoroughly the differential response of the two populations of mitochondria in both T1DM and T2DM, using both biochemical and proteomic tools, and thus improved our under- standing of the role of different mitochondrial populations in the pathogenesis of diabetic cardiomyopathy (Dabkowski et al, 2009;Baseler et al, 2010;Dabkowski et al, 2010).…”
Section: Mitochondrial Proteomics In T1dmmentioning
confidence: 99%